If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -9 = 3x Reorder the terms: -9 + 15x = 3x Solving -9 + 15x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -9 + 15x + -3x = 3x + -3x Combine like terms: 15x + -3x = 12x -9 + 12x = 3x + -3x Combine like terms: 3x + -3x = 0 -9 + 12x = 0 Add '9' to each side of the equation. -9 + 9 + 12x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 12x = 0 + 9 12x = 0 + 9 Combine like terms: 0 + 9 = 9 12x = 9 Divide each side by '12'. x = 0.75 Simplifying x = 0.75
| 9c+9.45=118.89 | | 1/4(8x-4)=10 | | 5(-7x-8)+3x=184 | | x-3x^(1/2)-18=0 | | 7z*2=9-3z | | 3cot^2x-6=0 | | 21x+28-2=10x+12 | | -x^3+20x+80=0 | | x-3x^(1/2)–18=0 | | 8x-32=14x-(2x+80) | | x+5+4x-60=90 | | 7.36x+16=54.1696+4x | | |1/3-2|=4 | | -z^3+20z+80=0 | | 6.7x+33.5=67 | | x-3x^(1/2)-2x^2–18=0 | | 4y-6=2y+y | | -6x-10y=5 | | X*9=36 | | .5x-5=0 | | (-x-2)*2= | | 4x-60-x+5=90 | | 6r^2-24=0 | | z^3-5z^2-16z=-80 | | 4x-60+x+5=180 | | -7/5x=28 | | (-x-2)= | | log(x^2)=8 | | 5-3(6-4x)=4+2(5x-3) | | 4x-60+x+5=90 | | (-x-2)2= | | z^3-5z^2+64=0 |